Metodologi Penulisan Kitab Al-Jami' Karya Imam Al-Tirmidhi: Tumpuan Kepada Meriwayat Hadis dalam Bab Tertentu - Sakat, Ahamad Asmadi (Jurnal Usuluddin, 2000)
The article discusses the methodology of Imam al-Tirmidhi in his Kitab al-Jami' for narrating hadiths and the use of specific symbols to indicate cross-references.